A Differential Fluorescent Receptor for Nucleic Acid Analysis. Issue 2 (11th December 2013) - Bengtson, Hillary N.; Kolpashchikov, Dmitry M.
Abstract Differential receptors use an array of sensors to recognize analytes. Each sensor in the array can recognize not one, but several analytes with different rates, so a single analyte triggers a response of several sensors in the array. The receptor thus produces a pattern of signals that is unique for each analyte, thereby enabling identification of a specific analyte by producing a "fingerprint" pattern. We applied this approach for the analysis of DNA sequences of Mycobacterium tuberculosis strains that differ by single nucleotide substitutions in the 81‐bp hot‐spot region that imparts rifampin resistance. The technology takes advantage of the new multicomponent, selfassembling sensor, which produces a fluorescent signal in the presence of specific DNA sequences. A differential fluorescent receptor (DFR) contained an array of three such sensors and differentiated at least eight DNA sequences. The approach requires only one molecular‐beacon‐like fluorescent reporter, which can be used by all three sensors. The DFR developed in this study represents a cost‐efficient alternative to molecular diagnostic technologies that use fluorescent hybridization probes.